PENINGKATAN MINAT BELAJAR SISWA MELALUI PENGGUNAAN VIRTUAL LAB PADA PEMBELAJARAN FISIKA MASA PANDEMI MATERI OPTIK DI KELAS XI MIPA 1 SMA NEGERI 1 PURI (BEST PRACTICE) - Abdul Kholiq (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Hasyim Asy'ari (Unhasy), 2021)
This research is an on-case study in the form of best practice which aims todetermine the responses and learning outcomes of students in class XI MIPA 1 SMANegeri 1 Puri Optical material through the use of a virtual lab. This research was carriedout in class XI MIPA 1 SMA Negeri 1 Puri involving 32 students consisting of 11 malestudents and 21 female students, carried out in April 2021. The research stages wereplanning, implementation (treatment), and observation (observation). The virtual lab usedutilizes learning media facilities at the Ministry of Education and Culture's learninghouse. The results showed that the learning process using a virtual optical material lab inclass XI MIPA 1 SMA Negeri 1 Puri gave positive responses to learning. Meanwhile,learning using a virtual lab gives results on the completeness of learning outcomes inPhysics of optical material in class XI MIPA 1 SMA Negeri 1 Puri. Complete learningoutcomes are achieved with a percentage of 90.6%.Keywords: interest in learning, virtual lab, optics.